Intermittent hypoxia exposure in a hypobaric chamber and erythropoietin abuse interpretation - Abellan, R.; Ventura, R.; Remacha, A. F.; Rodriguez, F. A.; Pascual, J. A.; Segura, J. (Journal of Sports Sciences, 2007)
The aim of this study was to assess the effect of intermittent hypoxia exposure on direct and indirect methods used to evaluate recombinant human erythropoietin (rhEPO) misuse. Sixteen male triathletes were randomly assigned to either the intermittent hypoxia exposure group (experimental group) or the control normoxic group (control group). The members of the experimental group were exposed to simulated altitude (from 4000 to 5500 m) in a hypobaric chamber for 3 h per day, 5 days a week, for 4 weeks. Blood and urine samples were collected before and after the first and the final exposures, and again 2 weeks after the final exposure. While serum EPO significantly increased after the first [from a mean 8.3 IU · l-1 (s = 3.2) to 16.6 IU · l-1 (s = 4.7)] and final exposures [from 4.6 IU · l-1 (s = 1.4) to 24.8 IU · l-1 (s = 9.3)], haemoglobin, percentage of reticulocytes, and soluble transferrin receptor were not elevated. Second-generation ON/OFF models (indirect rhEPO misuse detection) were insensitive to intermittent hypoxia exposure. The distribution of the urinary EPO isoelectric profiles (direct rhEPO misuse detection) was altered after intermittent hypoxia exposure with a slight shift towards more basic isoforms. However, those shifts never resulted in misinterpretation of results. The intermittent hypoxia exposure protocol studied did not produce any false-positive result for indirect or direct detection of rhEPO misuse in spite of the changes in EPO serum concentrations and urinary EPO isoelectric profiles, respectively.